Mortality and life-years lost due to alcohol: a comparison of acute and chronic causes - Chikritzhs, Tanya; Jonas, H.; Stockwell, Tim; Heale, P.; Dietze, P. (2001)
Objectives:(i)To estimate the numbers of deaths and person-years of life lost (PYLL) due to high-risk alcohol consumption in Australia during 1997,using current estimates of consumption. (ii) To compare the number of deaths and PYLL due to acute conditions associated with bouts of intoxication and chronic conditions associated with long-term misuse of alcohol.Methods: All Australian deaths during 1997 related to conditions considered to be partially or wholly caused by high-risk alcohol consumption were extracted from the Australian Bureau of Statistics Mortality Datafile and adjusted by alcoholic aetiologic fractions calculated for Australia in 1997. A life-table method was used to estimate the PYLL for deaths from alcohol-caused conditions.Main outcome measures: Numbers of all deaths and PYLL due to chronic and acute alcohol-related conditions.Results: Of the 3290 estimated alcohol-caused deaths in 1997,chronic coditions (e.g. alcoholic liver cirrhosis and alcohol dependence)accounted for 42%, acute conditions (e.g. alcohol-related road injuries and assaults)for 28% and mixed (chronic and acute) for 30%. of the 62914 estimated potential life years lost, acute conditions were responsible for 46%, chronic for 33% and mixed for 21%. The average number of years of life lost through deaths from acute conditions was more than twice that from chronic conditions, because the former mostly involved younger people.Conclusions: in view of the societal burdens imposed by premature deaths, more effective public health strategies are needed to reduce the harm associated with occasional high-risk drinking (as well as sustained high-risk drinking), especially among younger people.